A Review on Secured Network with Cryptographic Modelling - Suresh, A; Hemamalini, M (International Journal of Computer Sciences and Engineering, 2025)
In information network security is one of the most important elements because it is responsible for providing security to all information passed through network devices. System security includes the approval of access to information in a system and it will controlled by the system administrator. Cryptography gives secure correspondence within the sight of vindictive outsiders-known as foes. Cryptography is the way toward changing over standard plain text into cipher text. There are two sorts of cryptography they are symmetric and asymmetric. In symmetric frameworks use a similar key (the mystery key) to scramble and unscramble a message. In asymmetric frameworks use an open key to scramble a message and a private key to decode it. Utilization of uneven frameworks upgrade makes secure correspondence. Asymmetric frameworks incorporate RSA (Rivest-Shamir-Adleman), and ECC (Elliptic Curve Cryptography). The proposed framework utilizes AEDA calculation for information encryption as a result of its significant points on high security, bring down CPU time and less memory use. In AEDA Encryption and Decryption techniques can just scramble and decode a pixel value. The Encoding (converting message to a point) and Decoding (changing over a point to a message) are imperative capacities in Encryption and Decryption in AEDA